Rare bird documentation form for Bohemian Waxwing at Hickory Hill Park in Iowa City, 1978 - Halmi, Nicholas S.et al (1978)
Rare bird documentation form for a Bohemian Waxwing at Hickory Hill Park in Iowa City in Johnson County, IA on January 13, 1978. Epson - sheet feed